Assessing the potential cost‐effectiveness of retesting IHC0, IHC1+, or FISH‐negative early stage breast cancer patients for HER2 status. Issue 17 (17th June 2013) - Garrison, Louis P.; Lalla, Deepa; Brammer, Melissa; Babigumira, Joseph B.; Wang, Bruce; Perez, Edith A.
<x xml:space="preserve">Abstract</x> BACKGROUND Fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC) tests are commonly used to assess human epidermal growth factor 2 (HER2) status of tumors in patients with breast cancer. This analysis evaluates the likely cost‐effectiveness of expanded retesting to assess HER2 tumor status in women with early stage breast cancer. METHODS We developed a decision‐analytic model to estimate the incremental cost‐effectiveness ratio (ICER) of expanded reflex testing from a US payer perspective. Expanded reflex testing is defined as retesting tumor specimens from patients whose tumors are IHC0, IHC1+, or FISH‐negative on their first test. In the base case, we assumed that 80% of patient tumors are initially IHC‐tested and 20% are FISH‐tested. Testing outcomes for IHC and FISH with and without retesting were based on published meta‐analyses. The cost of tests and treatment and the long‐term health outcomes were obtained from the literature. RESULTS In the base case, we estimated that 2.27% of women who received expanded reflex testing would be HER2‐positive and receive trastuzumab treatment: the projected ICER was $36, 721 per life year or $39, 745 per quality‐adjusted life year (QALY). This varied between $47, 100 per QALY and $35, 500 per QALY if we assumed that 1%‐8% of patients retested were then HER2+, respectively. The results of deterministic and probabilistic sensitivity analysis were robust. This strategy would result in 4700 (2000‐17, 000) patients being eligible to receive trastuzumab treatment annually. CONCLUSIONS Retesting patients who are IHC0, IHC1+, or FISH‐negative is projected to be a cost‐effective clinical strategy. Cancer 2013;119:3113–3122. © 2013 American Cancer Society.